What microfinance schemes for women-owned microenterprises’ productivity in rural Benin? - FIAMOHE, ROSE; DEDEHOUANOU, SENAKPON FIDÈLE ANGE; Abdelkrim, Araar (My University, 2023)
Government and financial institutions are attempting to address the low financial inclusion for developing sustainable microenterprises in rural Benin. Yet, their actions remain to be guided by evidence pertaining to the design of financing schemes intended to boost rural women-owned enterprises. This paper focuses on the relationship between the various financing schemes that exist and the economic performance of women-owned enterprises in rural Benin, using a sample of 3949 small businesses. Results show that social network-based financing improves the business performance of rural women entrepreneurs in small-scale commerce. This is also the case for microenterprises managed by adult women and women with primary-school education. Formal credit-based financing increases the profit margins of mature microenterprises owned by women. This paper also shows that self-financing is more profitable for young rural women entrepreneurs. The results partly inform the need to target women more in financing policies in Benin.
Keywords: Microenterprise · Financial inclusion ·; Rural women · Benin